Evaluation of risk factors for surgical site infection after cesarean section - Dinçgez Çakmak, Burcu; Dündar, Betül; Turker, Ülkü; Temür, Muzaffer; Özdemir, Hacer; Üstünyurt, Emin; Özgen, Gülten (Journal of Surgery and Medicine, 2020)
Aim: Surgical site infection after cesarean section is an important and common health issue. Although there are several studies researching risk factors in the literature, limited data is present evaluating these factors in the Turkish population. In this study, we aimed to determine the risk factors and provide management protocols for the Turkish population. Methods: In this retrospective case-control study, 76 patients between 16-45 years of age who underwent cesarean section and were hospitalized for surgical site infection within 6 weeks and 149 patients who had no postpartum infection between June 2016 and December 2017 were included. Sociodemographic features, laboratory parameters, comorbid diseases and surgical characteristics were recorded. SPSS 21.0 was used for statistical analysis and P-value <0.05 was considered statistically significant. Results: The rate of surgical site infection requiring hospitalization was 1% (76/7590). In the infection positive group, body mass index and fasting blood glucose levels were higher (P<0.001 and P=0.021). Moreover, preoperative hemoglobin was lower and surgery time was longer in this group (P<0.001 and P=0.005). In logistic regression analysis, the risk of surgical site infection was found to increase by 1.4-fold with increased body mass index (OR 1.463, 95%CI 1.273-1.681, P<0.001) and 1.2-fold with higher fasting glucose level (OR 1.21, 95%CI 1.16-1.37, P=0.007). Patients with shorter surgery time (OR 0.749, 95%CI 0.709-0.789, P=0.010) and high preoperative hemoglobin levels (OR 0.532, 95%CI 0.408-0.695, P<0.001) had decreased infection risk. Conclusion: The risk factors of surgical site infection after cesarean section are generally modifiable. Thus, healthcare providers should inform patients for postpartum infection and risk factors during pregnancy and eliminate these factors if possible.